Exhaust gas condensate - formation, characterization and influence on platinum measuring electrodes in diesel vehicles - Binnig, Sabrina; Volpp, Hans-Robert (Sensors and actuators. B, Chemical, 2017)
Particle emission from diesel vehicles are subject to strict emission limits due to their harmful effects on humans and the environment. For this, soot particles are trapped in a diesel particulate filtering system (DPF) as part of the exhaust gas treatment. To monitor the DPF filtering efficiency throughout its lifetime, one possibility is based on a particulate matter sensor (PM-sensor) mounted downstream the DPF, collecting soot on its interdigital platinum electrodes. Besides soot particles, the electrodes can also be exposed to exhaust gas condensate which may accumulate throughout repeated cold starts and low load conditions. During sensor operation the temperatures are above the boiling point of water, whereby the water is vaporized and inorganic residues can remain on the sensing element and consequently changes in signal and surface are conceivable. To investigate this a test procedure at an engine test bench was developed to observe condensate formation and its transport within the exhaust gas system. In additional laboratory tests the impact of two condensates from diesel vehicles onto platinum measuring electrodes was investigated. SEM‐EDX was used for the sensing element surface analysis. Exhaust gas condensates were analyzed via ICP‐OES as well as IC. In the most exhaust gas condensates particularly transition metals with concentrations <10mg/L were verified. At a surface temperature of 100°C and a voltage of 45.6V electrophoresis occurred and the results show metallic deposits of iron on the surface of the cathode. Conductive dendrites containing copper, sodium and sulfur occurred in the gaps, which lead to an increasing current. Furthermore, sodium deposits influence the electric field between cathode and anode due to the formation of new electric potentials in the gaps whereby more soot is needed for the same signal which results in a decrease of the sensitivity and an increase of the resistance.
Gesehen am 09.08.2018
Available online 28 September 2016